Atypical Multiple Stab Injuries - A Case Report - Gunathilake, K.M.T.B.; Ranasinghe, C.E.; Vidanapathirana, M. (Proceedings of CFPSL 15th Annual Academic Sessions 2016/17, 2016)
Attached

INTRODUCTION : ' ’ j The usual weapons of stab injuries are knives, daggers, criss knives etc. These injuries could be I due to a large range of pointed weapons and they can produce different atypical stab injuries.! Sometimes, weapon is not available at the time of the autopsy, but when giving evidence, the - weapon is shown iand request to give opinion regarding the causative weapon. CASE HISTORY Elderly woman was found dead with multiple stab injuries inside a house. At autopsy examination,; there were 2 types of stabs. One was appeared as single injury on the body surface, but a paired stab somewhat oblique to each other (V shaped) was found inside the body. Along the upper, margin o]f one injury, there was a small semi-circular defect of the skin. The other type was paired stab injuries. There were 2 paired stab injuries. Paired Stabs somewhat' oblique to each other (V shaped) were separated with a septum. The police produced a knife as the weapon. CONCLUSIONS When the weapon is not available, the JMO has to reconstruct the causative weapon based on the findings while considering the possible differential diagnoses. V shaped paired stabs were compatible with a weapon which could be opened inside the body. Presence of single injury on the body surface with a paired stab inside the body were compatible with full penetration of the weapon In this case, the possible causative weapon was a Scissor.